A combined experimental and theoretical study on supramolecular assemblies in octahedral cobalt(III) salicylaldimine complexes having pendant side arms. (7th July 2016) - Ghosh, Kousik; Banerjee, Abhisek; Roy, Sumit; Bauzá, Antonio; Frontera, Antonio; Chattopadhyay, Shouvik
Graphical abstract: Meridional isomers of two mononuclear cobalt(III) complexes with salicylaldimine Schiff bases were prepared and characterized. The energetic features of conventional and unconventional supramolecular interactions have also been studied by means of DFT calculations. Abstract: Two mononuclear cobalt(III) complexes, [Co(L 1 )(N3 )2 (deen)] (1 ) and [Co(L 2 )(N3 )2 (DMSO)] (2 ), where HL 1 2-(2-(diethylamino)ethyliminomethyl)-4-bromophenol and HL 2 2-(2-(diethylamino)ethyliminomethyl)-6-methoxyphenol are tridentate and tetradentate Schiff bases, respectively and deen is a bidentate chelating ligand, N, N-diethyl-1, 2-diaminoethane, were prepared and characterized by elemental and spectral analysis. X-ray crystal structure determination confirmed their structures. Both complexes are meridional isomers. The solid state structures show the participation of the organic ligands in concurrent conventional and unconventional CH⋯π interactions along with hydrogen bonding. The energetic features of these interactions have also been studied by means of DFT calculations.